Art and merchandise in Keith Haring's Pop Shop - Raffel, Amy (New York, NY : Routledge, 2021)
"This book uses the Pop Shop, a previously overlooked enterprise, and artist merchandising to reconsider the significance and legacy of Haring's career as a whole, especially his career long pursuit of populism. Keith Haring developed an alternative approach to both the marketing and the social efficacy of art: he controlled the sales and distribution of his merchandise, while also promulgating his belief in accessibility and community activism. He proved that mass produced objects can be used as a strategy to form a community and create social change. Furthermore, looking beyond the eighties into the 1990s and 2000s, Haring and his shop prefigured artists' emerging, self-aware involvement with the mass media, and the art world's growing dependence on marketing and commercialism. The book will be of interest to scholars working in art history, consumer culture, cultural studies, media studies, and market studies. The book will be of interest to scholars or students studying art history, consumer culture, cultural studies, media studies, or market studies, as well as anyone with a curiosity of Haring and his work, the 1980s art scene in New York, the East Village, street art, art activism, and art merchandising"--
OCLC-licensed vendor bibliographic record.
Keywords: Haring, Keith -- Criticism and interpretation; Pop Shop (Retail store); Artists and community; Art, Modern -- 20th century -- Economic aspects; ART / History / Contemporary (1945-)